2014
DOI: 10.1111/ggi.12412
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex distribution in malignant and tuberculous serous effusions: A study of 127 patients and review of the literature

Abstract: Whereas malignancy in serous effusions is found in older and middle-aged people, tuberculous effusion is a disease of younger people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
3
6
0
1
Order By: Relevance
“…In the study, we found that male sex was a risk factor for TE. A possible explanation for it is that sex imbalance exists in TPEs 27,28 . Das DK et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, we found that male sex was a risk factor for TE. A possible explanation for it is that sex imbalance exists in TPEs 27,28 . Das DK et al .…”
Section: Discussionmentioning
confidence: 99%
“…Das DK et al . analyzed the sex distribution of TPE patients included in the previous published literatures, and most of studies (3/20) showed that female patients constituted the majority of TPEs (>50%) 28 . In the United States, from 1993 through 2003, 7,549 cases of pleural TB were reported, males comprised 67% and females 33% of the patient population.…”
Section: Discussionmentioning
confidence: 99%
“…20-55% of patients with pulmonary embolism have a pleural effusion. Bintcliffe, et al found that 70% of 126 patients with a pleural effusion did, indeed, have a single cause for it, but 30% had more than one cause [15].…”
Section: Pleural Effusion In Adults-etiology Diagnosis and Treatmentmentioning
confidence: 99%
“…29 (61,7%) pacijenata je pripadalo grupi ≥50 godina, dok je 18 (38,3%) pripadalo grupi ≥60 godina. Zaključak njegovog istraživanja je da se maligni pleuralni izlivi češće javljaju kod starijih i osoba srednjih godina i da su češći kod žena, a tuberkulozni izlivi se javljaju češće kod mlađih osoba [15].…”
Section: Diskusijaunclassified